Pakistan : The US, Geopolitics and Grand Strategies - Edited by Butt, Usama and Schofield, Julian (London Pluto Press, 2012)
International analysts and commentators consider Pakistan's position in the global geo-political order.
Include Glossary and Index
Keywords: United States -- Pakistan -- Diplomatic relations